2019
DOI: 10.1002/pssr.201900564
|View full text |Cite
|
Sign up to set email alerts
|

New Zero Poisson's Ratio Structures

Abstract: Most materials exhibit positive Poisson's ratio (PR) values, but special structures can also present negative and, even rarer, zero (or close to zero) PR. Null PR structures have received much attention due to their unusual properties and potential applications in different fields, such as aeronautics and bioengineering. Herein, a new and simple near‐zero PR 2D topological model is presented based on a structural block composed of two smooth and rigid bars connected by a soft membrane or spring. It is not base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We concentrated our study on the FDM printer since this methodology has been previously used in this kind of work. [ 5,6,75 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We concentrated our study on the FDM printer since this methodology has been previously used in this kind of work. [ 5,6,75 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] This potential has been exploited in a plethora of areas, like economy, [ 2 ] education, [ 3 ] and, in especial, it has contributed to a new perspective in materials science. [ 4–6 ] One of the interests of this field is to improve and/or to tune the mechanical properties of materials for applications in automotive, [ 7,8 ] aerospace, [ 9 ] civil, [ 10 ] and biomedical [ 11 ] fields, among others. In this sense, nature is a good source of inspiration, where we have many examples that structures, shapes, topologies, and hierarchical geometrical designs are parameters of fundamental importance to determine the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to NPR structures, cellular solids with zero Poisson's ratio (ZPR) have also gained attention, especially in shape-morphing applications [14][15][16]. Strongly strain-dependent Poisson's ratios in ZPR structure can also impose limitations on the structural performance since shape morphing materials and structures are, by design, expected to undergo large deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Young's modulus and Poisson's ratio of lattice structures have gained significant attention from the scientific community since these properties play a central role in a range of aforementioned mechanical applications. Recent studies have concluded that few geometries exhibit positive, negative, and zero Poisson's ratios, including extreme values and mixed mode (Olympio and Gandhi 2010, Attard and Grima 2011, Gong et al 2015, Chen et al 2018, Huang et al 2018, Wang 2019, Gaal et al 2020, Wang et al 2020. The main drawback of such lattices is that the elastic properties are a function of only geometric entities; hence upon manufacturing, it is not possible to change them, and due to this, the application of such lattices is limited to passive applications only.…”
Section: Introductionmentioning
confidence: 99%